Challenging with a critical exercise or the come back of a reading (Anclajes, 2011)
After the last dictatorship, the interest of literary criticism on the work of Ernesto Sábato has been scarce. For this reason, a new reading is proposed. This essay intends to explore the conditions that lead to the relationship between History and Myth, analysing the writing operations that determine the dual and apocalyptic world view of the writer. With this purpose, it focuses in his main novel, Sobre Héroes y Tumbas, and then it projects towards a general view of his literary work.
Keywords: Ernesto Sábato; Sobre héroes y tumbas; novel; history; mith